Do Spillovers Matter When Estimating Private Returns to R&D? - Eberhardt, Markus; Helmers, Christian; Strauss, Hubert (The Review of Economics and Statistics, 2013)
A large body of literature estimates private returns to R&D adopting the Griliches knowledge production framework, which ignores the potential impact of spillovers on consistent estimation. Using a panel of twelve manufacturing industries across ten OECD economies, we investigate whether ignoring spillovers leads to bias in the estimated private returns to R&D. We compare results from a common factor framework, which accounts for spillovers and other unobserved shocks, to those from a standard Griliches approach. Our findings confirm that conventional estimates conflate own-R&D and spillover effects, implying that spillovers cannot be ignored even when the interest lies exclusively in evaluating private returns to R&D.